Re-opening hairdressing salons, barber shops and gyms following COVID-19 lockdown: reducing risks from Legionella species through successful domestic steam disinfection of showerheads. Issue 5 (4th May 2021) - Millar, Beverley C.; Ferris, Jonalyn; Murphy, Alan; Reid, Norman; Moore, John E.
Abstract : Given the importance of disinfecting showerheads from Legionella species and the lack of instructions as to how to successfully achieve this, the aim of this study was to examine the ability of domestic steam disinfection to successfully disinfect showerheads from Legionella species. Steam disinfection of Legionella pneumophila [ n =3; L. pneumophila serogroup 2–15 (wildtype environmental water isolate); L. pneumophila serogroup 1 NCTC11192 (reference strain); L. pneumophila serogroup 1 (wildtype environmental water isolate)], L. erythra (wildtype environmental water isolate) and L. bozemanii CRM11368M (reference strain) were examined in this study. Steam disinfection employing a baby bottle steam disinfector device eradicated all Legionella organisms tested. Steam disinfection, when performed properly under the manufacturer's instructions, offers a relatively inexpensive, simple, versatile and widely available technology for the elimination of Legionella species from contaminated showerheads. We therefore advocate the employment of such devices to regularly disinfect showerheads and shower tubing in hairdressing salons, barber shops and gyms, as a critical control in the elimination of these organisms from these sources, thereby enhancing customer/client/staff safety.